OPTIMALISASI PERAN PENEGAK HUKUM DALAM PERLINDUNGAN TERHADAP ANAK-ANAK KORBAN KEKERASAN KOTA PADANG - Yusnita Eva; Firdaus; Witia Oktaviani (Faculty of Law, Universitas Gadjah Mada, 2021)
Abstract There seems to be an imbalance between regulations and the implementation of the law enforcement process in seeking justice for child victims of violence. The data from 2017 concerning the violence at the children at the municipality of Padang, as reported by the Police Department, reached 115 cases. This trend did not change, as shown by the cases between January and August 2018, when 77 child abuse cases were tabled to the court of the municipality. Only 36 cases in 2017 were submitted to the District Court for legal proceedings. Furthermore, from 2018 to September, only 17 cases were resolved by the District Court. This paper aims to explain the role of law enforcement in optimizing the law to protect the child and strengthen the function of the child protection institution, including DP3AP2KB and LPA. Further, it linked to the efforts that the judges and police have done as vanguards to defend the interests of the children. This study also shows that the role of the law enforcers remains the small function to be done. It is caused by the fact that this institution possessed limited authority. Likewise, the child protection institution carried out advocacy and the institutions did not have any authority to provide some legal advice. Intisari Terlihat adanya kesan ketidakseimbangan antara peraturan dan pelaksanaan proses penegakan hukum dalam mencari keadilan bagi anak-anak korban kekerasan. Data kekerasan kepada anak kota Padang tahun 2017 mencapai 115 kasus yang dilaporkan ke Polresta. Kasus kekerasan ini tidak mengalami penurunan sebab data tahun 2018 dari Januari sampai Agustus mencapai 77 kekerasan anak, hanya 36 perkara tahun 2017 yang masuk ke Pengadilan Negeri untuk diproses hukum. Selanjutnya tahun 2018 sampai September hanya 17 perkara yang diselesaikan pihak Pengadilan Negeri. Persoalan di atas menjadi tujuan untuk menjelaskan tentang peranan mereka dalam mengoptimalkan penegakan hukum terhadap perlindungan anak dan hubungannya dengan lembaga-lembaga perlindungan anak seperti DP3AP2KB dan LPA. Selanjutnya juga dikaitkan dengan upaya yang telah dilakukan oleh hakim dan polisi (PPA) sebagai garda terdepan yang membela kepentingan anak sebagai korban kekerasan. Faktanya, peran penegak hukum hanya sebagian kecil yang bisa terlaksana, disebabkan keterbatasan wewenang mereka dalam aturan. Begitu juga dengan lembaga-lembaga perlindungan anak, hanya sekedar melakukan advokasi dan tidak punya kewenangan untuk memberikan pertimbangan hukum.